Terapi Air Hangat untuk Menurunkan Tekanan Darah pada Ibu Hamil dengan Preeklamsia - Pratiwi, Dian; Horman, Sulistia; ., Wahyuni; Dompas, Robin; Adam, Yulien; Kuhu, Fonnie (JIDAN Jurnal Ilmiah Bidan, 2024)
Background: Preeclampsia is one of the causes of death in pregnant women. Preeclampsia can cause complications in mothers such as eclampsia (accompanied by seizures), placental abruption, subcapsular hemorrhage, disseminated intravascular coagulation (DIC), HELLP syndrome (hemolysis, elevated liver enzymes, and low platelet count), retinal detachment, heart failure, shock, and even death. Preeclampsia can also cause intrauterine fetal growth disturbances, affecting birth weight. There are several efforts to lower high blood pressure in pregnant women, namely pharmacological and non-pharmacological therapies. Objective: To determine the effectiveness of warm water therapy on blood pressure reduction in pregnant women with preeclampsia. Method: The type of research used in this study is Quantitative, employing a Pre-Experimental Research design with a one group pretest and posttest design. This design uses only one group of subjects or an intervention group. The sample used consisted of 16 respondents diagnosed with pregnancy-induced hypertension. Bivariate test using the Paired Sample T-test, Result: the statistical test shows a p-value = 0.000 < 0.05. It can be concluded that warm water therapy is effective in lowering the blood pressure of pregnant women with preeclampsia. It is hoped that this research can add information about the effectiveness of warm water therapy in lowering blood pressure in pregnant women with preeclampsia.